Analisis Implementasi Fatwa DSN-MUI Nomor 75 Tahun 2009 Tentang Kehalalan Produk Vaporizer dalam penjualan Langsung Berjenjang Syariah PT. BEST - Wijaya, Bagus Arta; Siswanto, Izzudin Edi (Journal of Fiqh in Contemporary Financial Transactions, 2024)
The aim of this research is to find out the halal law for vaporizer products in multi-level direct sales or sharia Multi Level Marketing (MLM). This research method uses qualitative field research by relying on interview techniques and documents that support the analysis of this research. The results of this research found that first, a Vaporizer (electric cigarette) is a device that works by heating liquid to produce vapor that is inhaled by the user. Second, PT Bandung Eco Sinergi Teknologi (BEST), a company that implements the PLBS system. PT. BEST sells various kinds of products, one of which is Vaporizer. Based on the results of the discussion, the law on Vaporizers traded by PT BEST is the same as Vaporizers sold in general because they use the same materials and are dangerous to health. It is recommended for PT BEST which implements the PLBS system not to sell products that are haram in terms of their substance or method of use.